Legal Analysis of Administrative Sanction Principles for Environmental Permit Abuse - Mukidi Mukidi (Faculty of Law, Universitas Pekalongan, 2021)
In the administrative legal system of a country, the granting of permits for certain types of business activities by the public is a authority held by the government. In the process of granting permits by the government, once the requirements set by individuals or legal entities within the community are met, there are certain principles that must not be violated by the permit recipients. Violations committed in the realm of state administration lead to administrative sanctions. These sanctions range from warnings, compensation, non-renewal of permits, and even revocation of permits to prevent the business from operating again. The abuse of the granted permits is often carried out by corporations in their activities related to environmental protection and management. The issuance of permits, while intended to facilitate operations, frequently becomes problematic and can have negative impacts on societal aspects such as health, education, and the economy. Laws related to environmental protection and management encompass provisions for written warnings. In cases of violations of environmental administrative laws, state administrative officials often issue written warnings. For instance, if there are violations of thresholds for air quality or emission standards. Additionally, the government can impose enforcement measures in the form of prevention and cessation of violations. For instance, if an individual or corporation is constructing a business establishment and disposing of waste without a permit.